Analisis Pemanfaatan Biobriket Dari Limbah Kulit Kopi Sebagai Basis Pengembangan Energi Terbarukan: Artikel Review - Sri Aulia Noprianti, Nadia; Hamdi, Hamdi; Yendri Sudiar, Nofi (Indonesian Society of Applied Science, 2024)
This review article aims to explore various techniques used in the production of biobriquettes from coffee skin waste with a variety of materials and methods. Based on the literature study conducted, several studies were found related to the production of biobriquettes from coffee waste using various methods such as briquetting, torefaction, and experimental methods. The main raw materials used include coffee grounds, coffee skin, paper, and sawdust. The adhesives used were tapioca flour, pine resin, and biotany flour. The results showed that the calorific value of the biobriquettes produced ranged from 3489-8180 calories/gram, with the highest value produced by certain composition variations. The biobriquettes produced generally meet SNI standards as an alternative fuel. This article is expected to provide a comparison between various methods and compositions in producing quality biobriquettes from coffee waste.